Reading “Guillelme l’Amïable”: Hypertextuality and La Prise d’Orange - Lucas Wood (Perspectives Médiévales)
The Old French epic poem La Prise d’Orange (late 12th-early 13th c.) systematically treats the conventional motifs, narrative patterns, characters and style of the chanson de geste with a comedic irreverence and an ironic distance that have led it to be labeled “the courtly parody of an epic,” but the text remains fundamentally organized by the generic paradigm from which it pointedly deviates. In Genettian terms, the Prise’s dominant hypertextual operation is travesty, which burlesques a prestigious text or story by recasting its characters and action in a ridiculously incongruous style—here, the narrative and rhetorical style associated with courtly discourse. The Prise cultivates a somewhat anxious enjoyment of its subversion of epic norms by thematizing the “folly” of its protagonist, Guillelme, whose absurd impersonation of a courtly lover casts doubt upon his legitimacy as an epic hero and the Prise’s “authenticity” as a chanson de geste. However, satirical transformation is ultimately reincorporated into the genre’s conservative narrative and ideological frameworks in a manner difficult to grasp through Genette’s system for lack of adequate distinctions between satire’s various possible ideological functions and stakes.